2018
DOI: 10.3390/su10103432
|View full text |Cite
|
Sign up to set email alerts
|

Architect, Catalyst, Advocate, and Prophet: A Four-Lens View of Companies to Support Ecodesign Integration

Abstract: Companies are increasingly expected to develop products with better environmental performance throughout their life cycle. Academic literature on ecodesign integration, which investigates firms’ practices of dealing with environmental concerns associated with their products, indicates a need for more focus on formal and informal organizational aspects. From the general management literature, the four-lens view of organizations provides a rich understanding of organizations by embracing their formal (structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…Researchers earlier mentioned how the level of formalization can influence DfS implementation in companies [31,57]. The interviews showed that each of the case companies approached DfS implementation differently.…”
Section: Degree Of Formalization In Dfs Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers earlier mentioned how the level of formalization can influence DfS implementation in companies [31,57]. The interviews showed that each of the case companies approached DfS implementation differently.…”
Section: Degree Of Formalization In Dfs Implementationmentioning
confidence: 99%
“…The company persona definition can help practitioners enrich the understanding of the maturity levels of the company in terms of its managerial preparedness and aspirations, thereby complementing the integration of the eco-design maturity model in practice. Another potential tool is the four-lens model for integrating sustainability in companies [57], which proposes a set of measures a company can take from four different perspectives-namely architect, catalyst, prophet, and advocate-to integrate sustainability in its activities. The company persona approach can help streamline the suggested course of action under each lens based on the niche characteristics of the company.…”
Section: Implications Of Company Persona Dimensionsmentioning
confidence: 99%
“…Ecodesign has emerged as a proactive approach to develop more eco-friendly products, and this concept has received a large number of definitions. Proponents of ecodesign in organizations generally include sustainability teams involved in the ecodesign agenda [8]. Nonetheless, ecodesign usually exceeds the environmental dimension of business performance [9] and enables opportunities for improvements in a range of projects [10].…”
Section: Introductionmentioning
confidence: 99%